Not without my daughter - Gilbert, Brian (Pasig City : Viva Video, 1991)
Two-time Oscar Winner Sally Field adds powerful acting triumph to her gallery of great roles in the suspense thriller Not Without My Daughter. She plays American tourist and homemaker Betty Mahmoody in a riveting true story of terror and escape. Betty has come to the Middle East with her daughter and native born husband (Alfred Molina of Species) for a visit with his family. But soon the horrible truth about their " vacation" surfaces, Betty's husband doesn't intend to bring his family back to America...ever. She may return, he says, but their daughter must stay. And he has centuries of local custom and the oppressive might of a police state behind him. As stranger in a foreign land, Betty has no money, no friends, no rights. But she does have an unconquerable will. In a hostile , war-torn country where even the slightest misstep can mean death, she makes a desperate bid to escape with her child. Her story, her courage and her ultimate triumph are unforgettable.